Status Gizi Dan Konsumsi Makanan Tinggi Lemak Jenuh Dengan Kejadian Penyakit Jantung Koroner Pada Pasien Rawat Inap RSJPD Harapan Kita Jakarta - Fikrianti, Nur; Ratnayani, Ratnayani; Khasanah, Tri Ardianti (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2024)
Background: Cardiovascular disease is the first rank of non-communicable disease that causes death in the world, one of which is Coronary Heart Disease (CHD). 35.6% of patients who have been treated in 2022 at Harapan Kita Cardiovascular Hospital are patients with CHD. Factors that can increase the risk of developing CHD include obesity and a diet high in saturated fat. Objective: To analyze the relationship between nutritional status and consumption of foods high in saturated fat with the incidence of CHD amongst pastients at Harapan Kita. Method: This study uses a cross-sectional design with a Chi-Square test involving 97 respondents. Results: There is a relationship between nutritional status and the incidence of CHD with p-value=0.037. There is no relationship between the frequency of consumption of foods high in saturated fat and the incidence of CHD with a p-value=0.363, and there is no relationship between the amount of saturated fat intake and the incidence of CHD with a p-value=0.67. Conclusion: As conclusions, there is a relationship between nutritional status and the incidence of CHD amongst patients and there is no relationship between consumption of foods high in saturated fat and the incidence of CHD amongst patients at Harapan Kita.